Gouvernance de l’eau potable et dynamiques locales en zone rurale au Bénin - Bernard G. Hounmenou (Développement Durable et Territoires, 2006)
In populations’ basic service supplying, the public policies, especially those of developing countries, have met deep changes in the last recent years. The most important changes are relative to the withdrawal of gratuitous public service. Beside the fundamental necessity of states to clean their economies, those reforms aim to favour populations’ participation in the management of operations linked to their needs satisfaction. The participation question constitutes actually a major element, for services organisation at community level. Indeed, several experiences have shown that the projects realised without the concerned populations’ participation, have failed at the execution moment, or by the lack of maintenance, they have led to negative results (Banque Mondiale, 1994). In Benin, certain development operations, especially those conducted in the drinking water supply sector, don’t escape to that reality. Indeed, until the end of the 1980’s, many drinking water supply equipment have been constructed by public authorities, without a real participation of rural area beneficiary communities. This situation has led to a lack of populations’ interest, expressed by the withdrawal of equipment in case of breakdown, and the turning to the use of non drinking water source. In order to remedy this situation, Benin Republic has opted in 1992 for a new national strategy of drinking water supply. This strategy aims the implication of rural area populations in the process of water supplying. The major principles of the strategy are among other things, the decentralisation of decision making process, as well as communities’ participation to investment and water point management. The materialisation of this willingness to improve the drinking water supply systems is expressed for example, by the communities joining through their contributions to equipment realisation and equipment management structures’ installation. The management structures’ tasks are among other things, the mobilisation of populations’ financial participation to equipment’ construction, the water price determination, the water sellers’ choice and the equipment’ management. The new strategy is also materialised by the arrival into the local system of drinking water governance in rural area, of new actors such as, local authorities, NGO, and water users organisations which have a functioning of ’’social enterprises’’. From empirical elements, this paper is focussed on the analysis linked to the socio-economic dynamic of actors implied in Benin rural populations’ water supply process.